United Arab Emirates (UAE) - Eapen, Valsamma (Int Psychiatry, 2008)
This paper will focus on the current state of mental health services in the United Arab Emirates (UAE) and reflect on the various public health, socio-economic and psychosocial factors that have a major impact on the mental health needs of the population. It is to be borne in mind that the services described in this paper are in a state of rapid change, as the country is witnessing one of the fastest rates of development in the world.